Conquering Bad Faith: The Moral-Psychological Recognition of Sartre's Absolute Responsibility - L`Esperance, Joseph R. (My University, 2005)
I examine Sartre's theory of responsibility and the phenomenon of bad faith in order to erect a theory of personal responsibility that is intended to operate as a possible recognition in one's moral-psychological life. I argue that our condition as fundamentally responsible and our avoidance of it in bad faith creates a dynamic that is immediately present in our individual and moral-psychological lives. The condition for the possibility of Sartre's particular sort of self-deception (bad faith) as well as the origin of absolute responsibility is Sartre's existential ontology. I argue that, because of the dynamic of bad faith and responsibility in which we are responsible in order to hide it, absolute responsibility is 'brought to the concrete' through our moral-psychological confrontation with bad faith. What this implies is not only the possibility of recognizing our absolute responsibility in the process of self-discovery or moral-psychological improvement, but also that this precedes and in fact is the necessary antecedent to the recognition of Sartre's much maligned radical freedom. There is a categorical differentiation between our ontological condition as freedom and the moral-psychological dynamic of responsibility recognition. In light of this, concrete freedom's definition as 'being conscious of ourselves as free', requires the recognition that we are fundamentally disconnected from what we are because we are the authors of what we are, i.e. responsible. Thus, responsibility recognition becomes the antecedent to authentic change. However, a methodology of how one may achieve responsibility recognition remains somewhat obscured because of the individuality of every human being that is inherent in an ontology that implies absolute authorship of ourselves and our world.
Keywords: Philosophy; Philosophy